The gene hunters - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1989)
Calestous Juma 1989.'The Gene Hunters : Biotechnology and the Scramble for Seeds' ISBN 0 86232 640 0.